Digital Childhoods Technologies and Children's Everyday Lives (International Perspectives on Early Childhood Education and Development,, 2018)
This book highlights the multiple ways that digital technologies are being used in everyday contexts at home and school, in communities, and across diverse activities, from play to web searching, to talking to family members who are far away. The book helps readers understand the diverse practices employed as children make connections with digital technologies in their everyday experiences. In addition, the book employs a framework that helps readers easily access major themes at a glance, and also showcases the diversity of ideas and theorisations that underpin the respective chapters. In this way, each chapter stands alone in making a specific contribution and, at the same time, makes explicit its connections to the broader themes of digital technologies in children's everyday lives. The concept of digital childhood presented here goes beyond a sociological reading of the everyday lives of children and their families, and reflects the various contexts in which children engage, such as preschools and childcare centres.